Hydrogen Production by Photoreforming of Organic Compounds - Rossetti, Ilenia; Bahadori, Elnaz; Villa, Alberto; Prati, Laura; Ramis, Gianguido (Journal of Technology Innovations in Renewable Energy, 2018)
H2 is gaining attention as energy vector, particularly if produced from renewable sources. It may be produced through photoreforming of organic compounds that act as hole scavengers to improve hydrogen productivity with respect to direct water photosplitting. Methanol is used here as model molecule to investigate the effect of catalyst composition and of substrate concentration on photocatalytic activity. Simple catalysts formulations were selected, in order to propose an easily scalable technology with a poorly expensive material. TiO2 with different structure (anatase, rutile and a mixture of them) was used as semiconductor, doped with a small amount of Au (0.1 wt%) to improve the lifetime of photogenerated charges. A new photoreactor was set up, with external irradiation that improves the scale up feasibility and possible future application with solar energy. Methanol conversion and hydrogen productivity increased with increasing methanol concentration up to 15 wt%. Rutile led to the highest conversion, but TiO2 P25 showed the highest hydrogen productivity. The best result was achieved by treating a 15 wt% methanol solution with 0.1 wt%Au/TiO2 P25, which led to 0.276 mol H2 h-1 kgcat-1.